(untitled) (KULT_online, 2018)
The multi- and interdisciplinary volume Disputed Memory. Emotions and Memory Politics in Central, Eastern and South-Eastern Europe provides a variety of case studies to display the complexity and specificity of disputed pasts in this region. By trying to overcome a methodological nationalism and a “representation bias” in the study of memory, the volume aims at understanding the mediation and transmission of memories in their social contexts. Furthermore, the authors integrate the role of emotions in processes of memory making and politics – at first sight a new and interesting approach. While the volume successfully displays transnational memory movements in Eastern and South-Eastern Europe, the analysis of emotions in the assembled texts could have benefitted from integrating methods and theories from the already rich sociological and historical literature on the study of emotions.